A Multimodal Approach to Analgesia in Anorectal Surgery - T. N. Garmanova; D. R. Markaryan; E. A. Kazachenko; A. M. Lukianov; M. A. Kazachenko; M. A. Agapov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Аim: Evaluation of methods for pain prevention and pain reduction after anorectal surgery at all stages of treatment based on publications found in available databases.Key points. Most anorectal diseases are benign and do not affect life expectancy, meanwhile about 40 % of the population suffer from it. Mainly anorectal disorders affect middle-aged people reducing their life quality. At the same time many articles aimed at studying only postoperative anesthesia. 2 researchers independently searched for articles published in Medline, Scopus, Cochrane, Web of Science, E-library databases using keywords. A total of 54 publications were included. A multimodal approach should include the pain prevention during pre-, intra- and postoperative periods. Acetaminophen is recommended for pain reduction according to the dosing protocols. Acetaminophen combined with other systemic analgesics is advisable for patients with severe pain. The opioids use is justified only for moderate-severe postoperative pain. Metronidazole and lidocaine with nitroglycerin ointment/ nifedipine/сorticosteroids effectiveness has been proven for local postoperative anesthesia. Prophylactic use of antibiotics and bowel preparation do not reduce postoperative pain. Stool softeners are recommended for reducing postoperative pain severity. Additional local anesthesia such as nerve blockade or infiltration anesthesia is recommended for all patients. Modern minimally invasive treatment methods of hemorrhoid are associated with less severe postoperative pain.Conclusion. The recommended scheme of multimodal anesthesia for patients after anorectal surgery is shown on Fig.1. Further studies are needed to evaluate preoperative anesthesia effectiveness, the feasibility of the perioperative flavonoids use, as well as comparisons of various minimally invasive treatment methods of anorectal diseases.